Designer Competency of the Fashion Design Undergraduate Students in Thailand: A Need Assessment Perspective - Kornchanok Boonthon; Thanin Ratanaolarn (My University, 2019)
Abstract This study used a mixed approach research design. The objectives were to study employers’ and college instructors’ needs regarding the designer competencies of undergraduate fashion-design students in Thailand, and to propose a guideline for the development of designer competencies of undergraduate fashion-design students in Thailand. For the quantitative approach, the research samples included 250 business owners/designers and 163 college instructors from fashion design faculties in Thai universities. A questionnaire was used as the research instrument. Data were collected by email. A “need-assessment analysis” technique was implemented in the data analysis. Regarding the qualitative approach, 15 key informants were interviewed via the interview script. A “content analysis” technique was used to analyse the qualitative data in this research. The results revealed that the employers’ need for improved components of knowledge competencies was consistent with the need of college instructors: both placed a priority on the development of language knowledge, followed by product-management knowledge, innovative knowledge and design knowledge. The employers’ need for improved components of skill competencies was consistent with the need of college instructors: both placed a priority on the development of language skills, followed by product-management skills, innovative and technology skills, and design skills. The employers’ need for improvement of qualification competencies was consistent with the need of college instructors: both placed a priority on the social role, followed by inner drive and self-conceptualisation, respectively. However, the findings indicated a difference between their needs: employers found that none of the qualification competencies needed rapid development, whereas college instructors indicated that one component needed rapid improvement – the social role.
Keywords: Needs analysis; Qualitative property; Research Design; Higher Education and Employability